Local Wisdom in Developing Communication and Collaboration Skills of Elementary School Students in the 21st Century: A Systematic Literature Review - Oktaviani, Ai; Melvina, Happy Ika; Kusnita, Dewi; Jamilah; Abdullah, Mohamad Syarief (International Journal Education and Computer Studies (IJECS), 2025)
Local wisdom, as an integral part of societal development, encompasses values preserved to meet needs and interactions with the environment, serving as an identity and reflection of cultural heritage passed down through generations. This study aims to explore the role of local wisdom in developing communication and collaboration skills among elementary school students in the 21st century through a systematic literature review (SLR). The research analyzed 25 relevant articles published between 2018 and 2023, selected based on inclusion criteria such as focus on local wisdom in education, relevance to 21st-century skills, and peer-reviewed accreditation. The findings indicate that integrating local wisdom values—such as mutual cooperation (gotong royong), deliberation (musyawarah), and tolerance—enhances students' communication and collaboration abilities by fostering cultural relevance and active participation in learning. The study concludes that local wisdom-based learning strategies are essential for addressing 21st-century educational challenges, offering practical implications for curriculum design and teacher training programs rooted in cultural contexts.